SOLATINA: A Latin-American society for bee research to foster the interactions between scientists and coordinate large-scale research programs - Antúnez, Karina (2018)
Bees (members of the super family Apoidea) are the main pollinators in modern agro-ecosystems, where they have a critical positive effect on yield improve ment for about 75% of world's crops (Klein et al., 2007; Potts et al., 2016). However, there is evidence of a worldwide decline in the populations of wild bees, and numerous reports of high colony losses of managed bees, which may disrupt crop pollination, honey produc tion and the reproduction of bee-polli nated wild plants (Potts et al., 2010), leading to negative social, economic and ecological effects (Potts et al., 2016). Latin America (hereafter, LA) is home to about 8 million managed honey bee colonies (Apis mellifera L.) which produce more than 200000 tons of honey annually (FAOSTAT, 2018). Several Latin American countries are among the global top 20 in terms of honey production and beehives stock, such as Argentina, Brazil and Mexico (García, 2018; Requier et al., 2018). Moreover, LA hosts a unique fauna of native bees, with about 5,000 identified species, including 391 species of the native stingless bees in the tribu Meliponini (Camargo & Pedro, 2008; Freitas et al., 2009). Some of those native stingless bees are managed since ancient times to produce honey through the practice of “Meliponiculture” (Jaffé et al., 2015). Latin American bee research has contributed to improve our understanding of problems relevant for apiculture, bee diversity and the causes of bee population decline in the region among other topics (see e.g., Maggi et al., 2016; Morales, Arbetman, Cameron, & Aizen, 2013; Vandame & Palacio, 2010). These scientific achievements are mostly the result of research efforts led by groups working independently rather than the product of cooperative research efforts between different countries. We argue that the strength, impact, and relevance of these research efforts, for apiculture and bees in the region, can be improved by promoting interactions between Latin American bee scientists and coordinating large-scale research programs.